Analisis Pelaksanaan Tugas Pokok dan Fungsi Tata Administrasi dalam Tata Administrasi Biro Umum Sekretariat Daerah Provinsi Lampung - Agus Purnomo; Ida Laila Maika (Universitas Bandar Lampung (UBL), 2023)
This study aims to identify and analyse the implementation of the main tasks and functions of the and inhibiting factors in the implementation of the main tasks and functions of the Lampung Province Regional Secretariat General Bureau in the coordination and implementation of budget management. The study uses a qualitative approach with the focus of research on the main tasks and functions of the Lampung Province Regional Secretariat General Bureau in the coordination and implementation of budget management. The results showed that the implementation of the main tasks and functions of the Lampung Provincial Regional Secretariat General Bureau in the coordination and implementation of budget administration had gone well according to the strategic plan of the Lampung Provincial Secretariat General Bureau, but the realisation had not succeeded in achieving the target of 100% as determined by achieving an average of 89.1%. Then, the factors that support the implementation of the main tasks and functions of the Lampung Provincial Secretariat General Bureau include communication, sources, trends or behaviours and bureaucratic structures, while the inhibiting factor consists of the content of the policy, information, support and potential distribution.